A Window into Italian Theatre: from Grotesque to Narrative Theatre. An Introduction - Pagliaro, Annamaria (Spunti e Ricerche, 2016)
As one reads any volume purporting to describe European theatre, one usually finds that it is narrated through a series of major playwrights unquestionably regarded as representative and as influential in the direction of theatrical activity. Yet their works, claimed by the various national theatres, are but a canonical representation, only one part of what really went on and what was popular in the theatre scene at the time of their production. More than telling a story of theatrical activity, such volumes construct a tale of exclusion, to some extent a misleading journey, plotted by a series of innovations, allegedly representing what was popular and the dominant trends at various given times. Thus the reader is led to believe that the development of theatre occurs as a linear and organic progression, and that what is being described through that selection of playwrights and works constitutes a cohesive history. Such an approach, however, has often failed to capture the actual relationship between the theatre and its audiences and it has certainly tended to exclude the many who engaged this medium with great enthusiasm and gained notable popularity in the course of their careers, as they artistically voiced the tension between art and life in compelling ways. When we turn to national theatres this approach is often replicated.